The past as a prologue: aspirations for the future portrayed in Chinese vernacular miniature monuments - Mengbi Li; Elmira Jamei (Journal of Asian Architecture and Building Engineering)
Whether to look to the past is a perennial dilemma, as the past evokes both terror and pleasure. Focusing on miniature monuments built for ancestors in the context of pre-modern China, this study reveals that while the peak period of production of miniature monuments occurred during the Han dynasty, the miniature monument building practice can be traced to living cases today. This paper highlights a phenomenon, a vision of the future imagined by descendants was integrated into a dialogue with the past through the agency of symbolic representations of buildings constructed for the deceased. Architecture, in this sense, acted as a facilitator of difficult communication with the deceased and conveyed profound desires that people strongly embraced but could not articulate. Such desires and dreams may not be accommodated in reality, but constructing miniature monuments in honour of ancestors reiterates that architecture is a spiritual home for brave imaginations and deep desires of people.